Pengaruh Environmental, Social, and Governance (ESG) Disclosure terhadap Kinerja Keuangan Perusahaan Sektor Energi yang Terdaftar di BEI Tahun 2021-2023 - Noor, Durratul Farrah; Maithy, Sifera Patricia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study examines the impact of Environmental, Social, and Governance (ESG) disclosure on the financial performance of energy sector companies listed on the Indonesia Stock Exchange. Using a quantitative approach, secondary data from annual and sustainability reports from 2021 to 2023 were analyzed using SPSS. The results indicate that, when considered simultaneously, ESG disclosure significantly influences financial performance, with a significance level of 0.035. However, in the partial analysis, each ESG component showed no significant effect on Return on Assets (ROA). These findings suggest that while ESG disclosure is essential for building investor trust, its direct impact on financial performance is not evident at an individual level. Therefore, it is recommended that companies more effectively integrate sustainability strategies into their operational frameworks to enhance long-term financial performance.